Предмет: Алгебра,
автор: roman11165
3^(y-2)+3^(y-1)+3^(y)=13/243
Ответы
Автор ответа:
0
3^(y-2)+3^(y-1)+3^y=13/243
3^y * (3⁻²+3⁻¹+1)=13/243
1 1
3^y * ( ---- + ---- + 1 ) =13/243
3² 3¹
1 3 9
3^y * (---- + ------ + -----) = 13/243
9 9 9
13 13
3^y * ------ = -------
9 243
13 9
3^y = ------- * --------
243 13
9
3^y = -------
243
1 1
3^y = ------- = --------- = 3⁻³
27 3³
y= -3
3^y * (3⁻²+3⁻¹+1)=13/243
1 1
3^y * ( ---- + ---- + 1 ) =13/243
3² 3¹
1 3 9
3^y * (---- + ------ + -----) = 13/243
9 9 9
13 13
3^y * ------ = -------
9 243
13 9
3^y = ------- * --------
243 13
9
3^y = -------
243
1 1
3^y = ------- = --------- = 3⁻³
27 3³
y= -3
Автор ответа:
0
cпс
Похожие вопросы
Предмет: Қазақ тiлi,
автор: salimaberezhko
Предмет: История,
автор: Neznakomec47
Предмет: Литература,
автор: demeuovashamshat
Предмет: Математика,
автор: 9080706050